2017
DOI: 10.1002/ceat.201700206
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Operating Strategies to Extend the Applications of Simulated Moving Bed Chromatography

Abstract: Chromatographic separation with solid stationary and fluid mobile phases is widely used to isolate and purify compounds. One of the most productive improvements in preparative chromatography is the simulated moving bed (SMB) process, which enables continuous feed supply and product removal by periodic operation of a multicolumn to simulate a countercurrent flow between the phases. The SMB process produces high‐purity compounds, even with low selectivity, and offers higher productivity and lower eluent consumpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 175 publications
(219 reference statements)
0
28
0
Order By: Relevance
“…Nevertheless. it was still possible to implement the SMB process for this separation task even with such low selectivity 34 …”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless. it was still possible to implement the SMB process for this separation task even with such low selectivity 34 …”
Section: Resultsmentioning
confidence: 99%
“…However, also the suggestion of completely new and probably partly unexpected non‐trivial configurations can be envisaged. Promising applications of superstructure analysis are already used to evaluate and optimize the large spectrum of modified more flexible new SMB process configurations as shown in .…”
Section: Discussionmentioning
confidence: 99%
“…In these stages, the costs and scale-up potential of the method become a very important issue to be considered [17]. There are prevailing resolution techniques and strategies to obtain the enantiomers in this scale including crystallization [29,30], simulated moving bed (SMB) [31], and liquid chromatography (LC) [14,22,27]. Leek H. et al [32] recently reported a strategy for large-scale isolation of enantiomers in drug discovery, affording different options that involved different chromatographic techniques together with crystallization.…”
Section: Trends In Chiral Separations On Preparative Scale In Early Pmentioning
confidence: 99%